Carboxylation of sodium arylsulfinates with CO2 over mesoporous K-Cu-20TiO2. Issue 2 (24th December 2021) - Chen, Yanjiao; Dai, Xuan; Zhang, Wenwei; Wu, Tao; Chen, Lei; Peng, Xinhua
Abstract : A mesoporous ternary metal oxide (K-Cu-20TiO2 ) from a simple sol–gel method was prepared to catalyze heterogeneously the carboxylation reaction of various sodium arylsulfinates under atmospheric carbon dioxide. Abstract : A mesoporous ternary metal oxide (K-Cu-20TiO2 ) from a simple sol–gel method was prepared to catalyze heterogeneously the carboxylation reaction of various sodium arylsulfinates under atmospheric carbon dioxide. The catalyst showed excellent selectivity and good functional group tolerance to carboxylation recycle. The oxidation state of active copper(i ) by characterization using FTIR, XRD, TG, XPS and TEM techniques proved to be efficacious to conduct atom economical reactions.